(3JcedI TQM LGeY GdJQePjs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s; (3CHh GdaJM GdjYeQjs
(3ChdgG (B:s
(3hdcfg djS Ydjg TQM jfGSHg hcJH Ydjg GdbGVi CHh HcQ Hf GdYQHi TQMg GdeSei HYGQVI GdGLhRi HGH eG LGA ai GdCQV cdgG eSLO s
(3BNQgG (B:s
(3jfJgi HhbaI cGJH (B( (3CKfGA GdLRA GdKGef Hbhdg (B: (3CKfGA HGH eG LGA ai GdJNTY ai GdUdGI (B) (3MOjK BNQ QhGg CHh YHO Gddg iGdJQePi GdMcje ai fhGOQ GdCUhd bGd Yf CHj gQjQI Yf QShd Gddg Udi Gddg Ydjg hSde Cfg QCi QLdkG jYHK HdMjJg ai UdGJg (B) s
(3fSNI fajSI LOkGs
(3cJHJ ai MjGg G deDdas
(3hYdjgG NWg HUMI GdSeGY SfI (B764(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B559s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs